Pendekatan Teologis dalam Kesenian Laesan Lasem: Analisis Dakwah Kultural - Umi Ghozilah; Aziz, Mokhamad Abdul; Suyadi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research discusses the theological approach in Laesan Lasem art with a qualitative method of text study. The purpose of this research is to explore information about the theological elements and theological flow in Laesan Lasem art in relation to Islamic theology. The results showed that Laesan Lasem art has content that has a deep philosophical meaning and contains theological elements in it. There are at least two elements of Islamic theology in Laesan Lasem art, namely about God and humans. The discussion of God contains faith in Allah and the Messenger and also implies the attributes of God. The discussion about humans relates to how humans get closer to God and the position of humans before God and humans. The description of the elements of theology in Laesan Lasem art includes three important points; faith, charity, and freedom of will. These three points have the same understanding as the Ash'ariyah school. The theological approach to Laesan can show that art is not only a cultural expression, but can also be a contextual and effective medium of da'wah. Through this approach, Laesan is not only maintained as a cultural heritage, but also empowered to convey Islamic values ​​beautifully and down to earth.